2021
DOI: 10.3390/ijms221910385
|View full text |Cite
|
Sign up to set email alerts
|

C9ORF72 Repeat Expansion Affects the Proteome of Primary Skin Fibroblasts in ALS

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterized by progressive degeneration of the corticospinal motor neurons, which ultimately leads to death. The repeat expansion in chromosome 9 open reading frame 72 (C9ORF72) represents the most common genetic cause of ALS and it is also involved in the pathogenesis of other neurodegenerative disorders. To offer insights into C9ORF72-mediated pathogenesis, we quantitatively analyzed the proteome of patient-derived primary skin fibroblasts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…In this regard, skin fibroblasts might be a suitable tissue model to assess functional cellular and bioenergetic impairment in C9ALS/FTD patients. In this context, previous studies have successfully used this tissue to mirror the alterations observed in C9orf72 neurons [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, skin fibroblasts might be a suitable tissue model to assess functional cellular and bioenergetic impairment in C9ALS/FTD patients. In this context, previous studies have successfully used this tissue to mirror the alterations observed in C9orf72 neurons [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with reports that C9ORF72 plays an important role in immune regulation (Burberry et al, 2016 ; O’Rourke et al, 2016 ; Sudria-Lopez et al, 2016 ), proteins associated with astrocytes and microglia were slightly enriched in ALS-C9 when compared to sporadic ALS (Umoh et al, 2018 ). Proteomic analysis of in vitro ALS/FTD-C9 models show that proteins involved in protein synthesis and protein degradation are predominantly affected (Hartmann et al, 2018 ; Lualdi et al, 2021 ). ALS-C9 patient-derived primary skin fibroblasts have altered expression of proteins involved in proteostasis including ribosomal proteins (RPL7 and RPL38), translation initiation and elongation factors (EIF3B, EIF4A1, EEF1A1, EEF1A2), members of the HSP90 family, proteasome 26S subunits and aminoacyl-tRNA synthetases (Lualdi et al, 2021 ).…”
Section: Als/ftd Models Of Diseasementioning
confidence: 99%
“…Proteomic analysis of in vitro ALS/FTD-C9 models show that proteins involved in protein synthesis and protein degradation are predominantly affected (Hartmann et al, 2018 ; Lualdi et al, 2021 ). ALS-C9 patient-derived primary skin fibroblasts have altered expression of proteins involved in proteostasis including ribosomal proteins (RPL7 and RPL38), translation initiation and elongation factors (EIF3B, EIF4A1, EEF1A1, EEF1A2), members of the HSP90 family, proteasome 26S subunits and aminoacyl-tRNA synthetases (Lualdi et al, 2021 ). These findings are consistent with proteomic studies from primary mouse cortical neurons overexpressing poly-(PR) 175 , one of the five possible peptides produced via RAN translation, which show significant reduction in cytosolic ribosomal proteins that corresponded with a reduction in synaptic and axonal proteins (Hartmann et al, 2018 ).…”
Section: Als/ftd Models Of Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence point to differences in sALS skin compared to controls, such as increased collagen density (12,13), increased MMP-2 and MMP-9 (14,15), increased S100A4 (16), and an altered aging metabolism phenotype (17). Furthermore, ALS skin and fibroblasts have been shown to recapitulate pathology thought to play key roles in neuronal death, such as SOD1 misfolding (18), FUS (19) and TDP-43 (20)(21)(22)(23)(24)(25)(26)(27) pathology, mitochondrial dysfunction (28)(29)(30), abnormal stress granule formation (31,32) and RNA processing (33), as well as altered protein homeostasis in the case of C9Orf72 mutant fibroblasts (34).…”
Section: Introductionmentioning
confidence: 99%